Loss of the IL-27R Results in Enhanced Tubulointerstitial Fibrosis Associated with Elevated Th17 Responses - Coppock, Gaia M (J Immunol, 2020)
Clinical and experimental studies have established that immune cells such as alternatively activated (M2) macrophages and Th17 cells play a role in the progression of chronic kidney disease (CKD), but the endogenous pathways that limit these processes are not well understood. The cytokine IL-27 has been shown to limit immune-mediated pathology in other systems by effects on these cell types, but this has not been thoroughly investigated in the kidney. Unilateral ureteral obstruction (UUO) was performed on WT and IL-27Rα(−/−) mice. After two weeks, kidneys were extracted, and the degree of injury was measured by hydroxyproline assay and quantification of NGAL mRNA. Immune cell infiltrate was evaluated by immunohistochemistry and flow cytometry. An anti-IL-17A monoclonal antibody was subsequently administered to IL-27Rα(−/−) mice every two days from day of surgery with evaluation as described after two weeks. After UUO, IL-27 deficiency resulted in increased tissue injury and collagen deposition, associated with higher levels of chemokine mRNA and increased numbers of M2 macrophages. Loss of the IL-27Rα led to increased infiltration of activated CD4(+) T cells that co-produced IL-17A and TNFα, and blockade of IL-17A partially ameliorated kidney injury. Patients with CKD had elevated serum levels of IL-27 and IL-17A, while expression of transcripts for the IL-27RA and the IL-17RA mRNA in the tubular epithelial cells of patients with renal fibrosis correlated with disease severity. These data suggest that endogenous IL-27 acts at several points in the inflammatory cascade to limit the magnitude of immune-mediated damage to the kidney.